Impact of physical activity on Chinese college students’ “going into the world” psychology: chain mediating effects of hardiness and positive academic emotions - Guo, Xiangxuan; Cao, Dawei; Bai, Donghuan; Wu, Dong; Kuang, Lulu (Frontiers in Psychology, 2025)
IntroductionBased on positive psychology and emotion regulation theory, this study constructed a chain mediation model to explore the mechanism through which physical activity influences Chinese college students’ “Going into the World” psychology, specifically examining the mediating roles of hardiness and positive academic emotions.MethodsA total of 755 college students were surveyed using cluster random sampling. The instruments employed included the Physical Activity Rating Scale-3 (PARS-3), the Hardiness Scale (HS), the Academic Emotions Questionnaire (AEQ), and the Scale of Going into the World (SGIW). Data were analyzed using correlation analysis, regression analysis, and bootstrap mediation tests (Model 6, 5000 samples).ResultsCorrelation analysis revealed significant positive correlations between physical activity, hardiness, positive academic emotions, and “Going into the World” psychology. Regression analysis indicated that physical activity not only directly and positively predicted “Going into the World” psychology (B = 0.1489, p < 0.001) but also significantly predicted hardiness and positive academic emotions. Mediation analysis using the Bootstrap method confirmed significant indirect effects via three pathways: the independent mediating effect of hardiness (Effect = 0.0415, 95% CI [0.0249, 0.0621]), the independent mediating effect of positive academic emotions (Effect = 0.0086, 95% CI [0.0015, 0.0205]), and their chain mediating effect (Effect = 0.0039, 95% CI [0.0006, 0.0108]). The total mediating effect accounted for 26.61% of the overall effect, with hardiness exhibiting a more substantial mediating role.DiscussionThe results indicate that physical activity enhances college students’ “Going into the World” psychology both directly and indirectly by improving their hardiness and positive academic emotions. This study provides a theoretical foundation and practical pathways for promoting college students’ mental health and social adaptation through physical activity interventions, highlighting the particular importance of fostering psychological hardiness.